ANALISIS VALUE CHAIN KOMODITAS BUAH NANAS (Studi Kasus Desa Tangkit Baru Kecamatan Sungai Gelam di Muaro Jambi) - Galuh Diva Nabina; Zulfanetti; Jaya Kusuma Edy (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the farming conditions and value chain of pineapple commodities in Bangkit Baru Village. The focus of this research includes farmer characteristics, production patterns, distribution channels, and strategies to improve the competitiveness of pineapple commodities through the value chain approach and SWOT analysis. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation involving farmers, collectors, and marketing actors. The results of the study show that most pineapple farmers in Bangkit Baru Village are male, with the majority having a senior high school (SMA) educational background. Land ownership and production outputs are fully privately owned, and farming management systems are still simple and largely depend on family labor. The average farming experience ranges from 10 to 20 years, with the dominant land area owned being 1 hectare. Production costs range from Rp1.000.000 to Rp5,000.000 per planting season, while the selling price of pineapple ranges from Rp3.500 to Rp5.000 per kilogram. The pineapple value chain shows a relatively stable marketing pattern, with established relationships between farmers, collectors, traders in local and external markets, and final consumers. However, product improvement strategies are still considered less aggressive, as there are several weaknesses that may become threats, such as rat pests and unpredictable weather conditions that hinder the production process.